PENGARUH PENERAPAN MODEL COOPERATIVE SCRIPT DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 BASA AMPEK BALAI TAPAN KABUPATEN PESISIR SELATAN - Yohanda, Early; Anggraini, Villia; Yuliana Fitri, Dewi (Pendidikan Matematika, 2013)
Background of this research was students understanding of mathematical concept and students rarely make a summary of the materai provide by the teacher. Study was to examine students understanding of mathematical concept using a model of cooperative script with handout is better than the students understanding of mathematical concepts using conventional learning ". This type of research is experimental research, wich used subject random. The population in this study were students of class VIII SMP 2 Basa Ampek Balai Tapan in the Academic Year 2013/2014. The result of hypothesis test was accept Â = 0.045 < Î± = 0.05, so hypothesis was accepted. It can be concluded that understanding of mathematical concepts in aplliying cooperative Script with Handout better than the understanding of mathematical concept students in conventional learning.